Cell‐Free Protein Synthesis in Bifunctional Hyaluronan Microgels: A Strategy for In Situ Immobilization and Purification of His‐Tagged Proteins. Issue 3 (4th May 2020) - Heida, Thomas; Köhler, Tony; Kaufmann, Anika; Männel, Max J.; Thiele, Julian
Abstract: The front cover artwork is provided by the Thiele group at Leibniz IPF Dresden (Germany). The image shows a microgel hosting cell‐free synthesis of green fluorescent protein. Despite its open, membrane‐free nature, the multifunctional microgel is also able to trap proteins inside its polymer matrix. Read the full text of the Article at 10.1002/syst.201900058 . Abstract : "Mimicking cellular life while combining production, separation, and purification of biomolecules on a single platform is a key step towards truly applicable cell‐like biosynthesis. To achieve simultaneous synthesis and immobilization of proteins, both DNA encoding for His‐tagged proteins and Ni‐activated NTA moieties that effectively bind such proteins are linked to microfluidically prepared microgels, which are loaded with an extracted protein synthesis machinery. Most importantly, as‐formed proteins remain inside the microgels despite the absence of a membrane‐like barrier, as commonly utilized in artificial cell design…" This and more about the story behind the front cover can be found in the Article at 10.1002/syst.202000058 .